Surviving the turbulence: a retrospective account of designedpolicies for mitigating the spread of COVID-19 in Ghana - Assibey, Ginn Bonsu (Taylor and Francis, 2024)
Several policies were designed during the COVID-19 pandemic to control the virus from spreading. However, little is known about the nature of the designed policies and how the citizens lived with the designed policies in Ghana. This paper attempts a retrospective exploratory account of the COVID-19 policies in Ghana through an amalgamation lens of design matrix and activity theory from 15March to 10 July 2020. The population for the study was the COVID-19 policies adopted by Ghana. Out of 16 countries in West Africa with COVID-19 cases, Ghana was selected due to the online avail-ability of its COVID-19 policies and the fact that the policies were in English. Content analysis was used to gather data on Ghana COVID-19 policies and innovative scenarios used for living with the designed policies. The results show that the designed policies adopted a top down approach and were difficult for the citizens to live with but most were adjusted later, which triggered social and economic challenges for the citizens and were to some extent mitigated by the government and the citizens through innovations. Therefore, the government should leverage ideas from the citizens and engage social designers in policy design through the proposed hybrid-designed model.